Greater eccentric exercise-induced muscle damage by large versus small range of motion with the same end-point - Fochi, A. G.; Damas, F.; Berton, R.; Alvarez, I.; Miquelini, M.; Salvini, T. F.; Libardi, C. A. (Biology of Sport, 2016)
Several factors can affect the magnitude of eccentric exercise (ECC)-induced muscle damage, but little is known regarding the effect of the range of motion (ROM) in ECC-induced muscle damage. The purpose of this study was to investigate whether elbow flexor ECC with 120° of ROM (from 60° of elbow flexion until elbow full extension - 180° [120ROM]) induces a greater magnitude of muscle damage compared with a protocol with 60° of ROM (120-180° of elbow flexion [60ROM]). Twelve healthy young men (age: 22 ± 3.1 years; height: 1.75 ± 0.05 m; body mass: 75.6 ± 13.6 kg) performed the ECC with 120ROM and 60ROM using different arms in a random order separated by 2 weeks and were tested before and 24, 48, 72 and 96 h after ECC for maximal voluntary isometric contraction torque (MVC-ISO), ROM and muscle soreness. The 120ROM protocol showed greater changes and effect sizes (ES) for MVC-ISO (-35%, ES: 1.97), ROM (-11.5°, ES: 1.27) and muscle soreness (19 mm, ES: 1.18) compared with the 60ROM protocol (-23%, ES: 0.93; -12%, ES: 0.56; 17°, ES: 0.63; 8 mm, ES: 1.07, respectively). In conclusion, ECC of the elbow flexors with 120° of ROM promotes a greater magnitude of muscle damage compared with a protocol with 60° of ROM, even when both protocols are performed at long muscle lengths.